Ernest Reig Martínez (Dir.), Matilde Mas Ivars, Elisenda Paluzie i Hernández, Jordi Pons Novell, Javier Quesada Ibáñez, Juan Carlos Robledo Domínguez y Daniel A. Tirado Fabregat: Competitividad, crecimiento y capitalización de las regiones españolas - Arauzo-Carod, Josep María (Investigaciones de Historia Económica, 2019)
Sin resumen